Protective effects of human umbilical cord mesenchymal stem cell-derived conditioned medium on ovarian damage. (19th November 2019) - Hong, Liming; Yan, Long; Xin, Zhimin; Hao, Jie; Liu, Wenjing; Wang, Shuyu; Liao, Shujie; Wang, Hongmei; Yang, Xiaokui
Abstract: Chemotherapeutic agents are extensively used to treat malignancies. However, chemotherapy-induced ovarian damage and reduced fertility are severe side effects. Recently, stem cell transplantation has been reported to be an effective strategy for premature ovarian insufficiency (POI) treatment, but safety can still be an issue in stem cell-based therapy. Here, we show the protective effects of human umbilical cord mesenchymal stem cell-derived conditioned medium (hUCMSC-CM) on a cisplatin (Cs)-induced ovarian injury model. hUCMSC-CM can relieve Cs-induced depletion of follicles and preserve fertility. In addition, hUCMSC-CM can decrease apoptosis of oocytes and granulosa cells induced by Cs. RNA sequencing analysis reveals the differentially expressed genes of ovaries after Cs and hUCMSC-CM treatments, including genes involved in cell apoptosis. Furthermore, we show that the granulocyte colony-stimulating factor (G-CSF)/phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) pathway plays an important role in protecting granulosa cells from Cs-induced apoptosis. Together, we confirm the protective effects of hUCMSC-CM on ovarian reserve and fertility in mice treated with Cs, highlighting the remarkable therapeutic effects of hUCMSC-CM.